2007
DOI: 10.1111/j.1365-2796.2007.01777.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of inflammation on epigenetic DNA methylation – a novel risk factor for cardiovascular disease?

Abstract: Objective. The lifespan of dialysis patients is as short as in patients with metastatic cancer disease, mainly due to cardiovascular disease (CVD). DNA methylation is an important cellular mechanism modulating gene expression associated with ageing, inflammation and atherosclerotic processes.Design. DNA methylation was analysed in peripheral blood leucocytes from three different groups of chronic kidney disease (CKD) populations (37 CKD stages 3 and 4 patients, 98 CKD stage 5 patients and 20 prevalent haemodia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
254
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 350 publications
(268 citation statements)
references
References 30 publications
12
254
1
1
Order By: Relevance
“…Hodge et al (197) have demonstrated that the inflammatory cytokine IL-6 might exert an impact on epigenetic changes in cells via regulation of a DNA methyltransferase gene. In accordance, we demonstrated that global DNA hypermethylation was associated with inflammation and increased mortality in CKD (198). As we also find Figure 4.…”
Section: Epigenetics-the Science Of Changesupporting
confidence: 77%
“…Hodge et al (197) have demonstrated that the inflammatory cytokine IL-6 might exert an impact on epigenetic changes in cells via regulation of a DNA methyltransferase gene. In accordance, we demonstrated that global DNA hypermethylation was associated with inflammation and increased mortality in CKD (198). As we also find Figure 4.…”
Section: Epigenetics-the Science Of Changesupporting
confidence: 77%
“…There are dynamic changes in the DNA methylation pattern during the lifetime and several environmental factors such as dietary compounds [12], oxidative stress [15], hypoxia [36], inflammation [37] or ageing [35] may affect methylation status and modify gene expression. Thus, changes in the DNA methylation pattern as a result of dietary treatments or conditions have been studied in the last years, comparing vegetarians with omnivores [39], the effects of different obesogenic diets [26,31] or different dietary treatments to lose weight [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies also indicated a good correlation between levels of leukocyte DNA methylation and degrees of inflammation, suggesting DNA methylation may represent a novel pathway underlying the association between obesity, inflammation and cancer risk. 19,20 Although BMI is the most commonly used measure for obesity, it does not adequately capture body fat mass and the distribution of body fat. We characterized body composition using % body fat and areas of subcutaneous fat (SAT) and visceral fat (VAT) (cm 2 ).…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%